Transformasi dari Kertas ke Elektronik: Telaah Yuridis dan Teknis Sertipikat Tanah Elektronik - Dian Aries Mujiburohman (BHUMI: Jurnal Agraria dan Pertanahan, 2021)
Abstract: A land certificate is an official document issued by the Land Registry. This document is proof of ownership of a piece of land.  In Indonesia, it usually comes together with a land book (Buku Tanah), a document in the form of a list providing juridical and physical data of a piece land whose ownership has been registered. . A certificate is the final product of land registration processes, which includes the process by electronic means. The  certificate can both be issued in the form of printed document or digital document . The development of digital land certificate drove  this research in analyzing the juridical and technical aspects of electronic certificates. The method used is normative legal research with a statutory regulatory approach. The results of this study indicate that in the juridical aspect of the Government Regulations on the E-Certificate,especially regarding the implementation,  is not based on The Basic Agrarian Law (UUPA) as well as its implementing regulations. The implementation follows The ITE Law and The Job Creation Law (with PP No.18/2021 as the primary source of the law) instead. The technical aspect of E-Certificate, when viewed from safety factor, gives more certainty than the ones with analogsystem.. It is particularly due to the use  of a digital signature encoded by a cryptographic algorithm  protected by a certain code (Hash Code and QR Code). Consequently, only people who have authorities can access it. Keywords: electronic land certificate, electronic documents, land registration, digital signature Intisari: Pada dasarnya, sertipikat tanah merupakan surat tanda bukti hak yang berupa salinan buku tanah dan surat ukur yang telah disatukan. Sertipikat merupakan produk akhir dari semua proses pendaftaran tanah, hal terpenting adalah proses pendaftaran dari awal hingga akhir dengan cara elektronik. Sertipikat dapat diterbitkan dalam bentuk fisik/cetak kertas maupun digital/elektronik. Melihat perkembangan tersebut, tujuan penelitian ini hendak menganalisis aspek yuridis dan teknis sertipikat elektronik. Metode yang digunakan ialah penelitian hukum normatif dengan pendekatan peraturan perundang-undangan. Hasil penelitian menunjukkan bahwa dari segi aspek yuridis Permen Sertipikat-el khususnya terkait pelaksanaan Sertipikat-el tidak berdasarkan sumber hukum utama yaitu UUPA dan peraturan pelaksananya, namun mengacu pada UU ITE dan UU Cipta Kerja, sumber hukum utamanya terbit belakangan yaitu PP No. 18 Tahun 2021, namun PP tersebut juga sebagai ketentuan pelaksana dari UU Cipta Kerja. Dalam aspek teknis sertipikat-el jika dilihat dari faktor keamanan lebih terjamin dibandingkan sertipikat analog, salah satunya menggunakan digital signature yang disandikan algoritma kriptografi dengan dilindungi dengan kode tertentu (Hash Code dan QR Code), dengan demikian hanya orang yang memiliki otoritas yang dapat mengaksesnya.  Kata Kunci: Sertipikat Tanah Elektronik, Dokumen Elektronik, Pendaftaran Tanah, Tanda Tangan Elektronik.